The effect of humidity on peak value of HEMA carbonyl absorbance band - Adioro Soetojo (Dental Journal (Majalah Kedokteran Gigi), 2006)
Bond strength between 2-Hydroxyethyl methacrylate HEMA-based dentin bonding agent and dentin collagen had proved by presence of the chemical interaction. This union involved the carbonyl group on HEMA resin with amino group on dentin collagen following produce an amide chain. However, this bond strength influence by humidity condition of dentin collagen and HEMA resin. The aim of this study is to measure the effect of humidity on peak value of the HEMA carbonyl absorbance band. The bond strength between by HEMA bonding agent and dentine collagen was analyzed in different humidity, e.g. in 60%, 70%, 80%, and 90% humidity. Control experiment was done in ambient room humidity that is 65%. Chemical bond that formed between HEMA and dentine collagen was carried out by mixing pure HEMA with bovine type-I collagen which had been stored in different humidity. The esther carbonyl group of HEMA will react with the amino group of collagen, produced an amide bonding, which is observed by measuring the IR spectrum absorbance of the esther carbonyl group of HEMA in KBr method. The decrease of the carbonyl group absorbance indicates the more chemical bonds formed. By measuring the absorbance of C=O esther in different humidity, it showed that the greatest number of chemical bonds resulted when the experiment was done in 70% humidity condition.